English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

x(squared) -4x+4 = -11/3+4 becomes
(x-2)(squared) = 1/3
I understand I needed to factor to get the first part but I dont see how to get the 1/3...

hopefully you can understand, the computer doesnt really give me the option to write it correctly, thanks!

2007-06-10 13:19:05 · 5 answers · asked by Devin G 2 in Science & Mathematics Mathematics

5 answers

4 = 12/3

-11/ 3 + 12/ 3 = 1/3

2007-06-10 13:22:05 · answer #1 · answered by richardwptljc 6 · 0 1

x^2 - 4x + 4 = -11/3 + 4

Complete the squares on the left side:
(x - 2)^2 = -11/3 + 12/3
(x - 2)^2 = 1/3

2007-06-10 20:29:03 · answer #2 · answered by Kemmy 6 · 0 0

lets look at the part of the problem that is bothering you.

you have to remember how to maninpulate fractions.
-11/3+4=-11/3+3*4/3=-11/3+12/3
so we have a common denominator and now we can add the numerators getting
-11/3+12/3=(12-11)/3=1/3

fininshing the problem
take the square root
x-2=plus or minus sqrt(1/3) or x=2 plus or minus sqrt(1/3)

2007-06-10 20:32:18 · answer #3 · answered by careyschwartz 2 · 0 0

x^2 - 4x + 4 = -11/3 + 4
(x - 2)^2 = (-11 + 12) / 3
(x - 2)^2 = 1/3.

2007-06-10 20:28:47 · answer #4 · answered by Anonymous · 0 0

x^2 -4x+4 = -11/3+4
(x-2)^2 = 1/3
x-2 = +/- sqrt(1/3)
x = 2 +/- sqrt(1/3)
x = 2 +/- sqrt(3)/3

2007-06-10 20:27:44 · answer #5 · answered by ironduke8159 7 · 0 0

fedest.com, questions and answers